“After reducing alcohol, things now work well at home”: Perceived impacts of the Mlambe intervention on alcohol use, relationship dynamics, household economics, and HIV treatment adherence in Malawian couples - Sarah A. Gutin; Nancy Mulauzi; Jane Jere; Cobbener Sungani; Scott Tebbetts; Allison Ruark; James Mkandawire; Amy A. Conroy (PLoS ONE, 2025)
Unhealthy alcohol use is prevalent in sub-Saharan Africa and can worsen poverty, couple relationships, and HIV treatment outcomes. In response, we assessed participant experiences with Mlambe, a pilot study of an economic and relationship-strengthening intervention for couples living with unhealthy alcohol use and HIV. Exit interviews were conducted with a subset of 20 couples who participated in a pilot trial of Mlambe in Zomba, Malawi. A 10-month intervention consisted of financial literacy and couples counseling sessions and incentivized savings accounts. Eligible couples were married, ≥ 18, with at least one partner with unhealthy alcohol use (according to AUDIT-C screen), and currently on antiretroviral therapy (ART). Interviews were recorded, transcribed, translated, and analyzed using dyadic framework analysis. Intervention couples reported that alcohol use caused many problems and that reducing or quitting use brought improvements to their physical and emotional health, and the well-being of their marriages and households. Before Mlambe, couples reported that quarrels about alcohol use were common. After the intervention, couples reported improvements to their relationships and less alcohol use, which led to more open and respectful couple communication and other marital improvements including increased sexual satisfaction and trust. Women and men described that post-intervention, men reduced spending on alcohol which improved availability of money for household needs such as food and clothing, and that feeling more economically secure reduced stress and led to a more “peaceful family.” After Mlambe, male drinkers described more motivation to pursue income-generating activities, and that reduced alcohol use led to greater medication adherence as they no longer forgot to take ART when drinking. Mlambe may contribute to positive change for couple relationships and health behaviors through mechanisms including reduced conflict and poverty related to reduced alcohol use. The model appears promising for couples in resource-poor settings where HIV, poverty, and alcohol use are mutually reinforcing.